DESIGN OF THE MANAGEMENT MODEL OF URBAN HOUSEHOLDS SOLID WASTE GENERATION - Sabara, Zakir; Hafid, Muhammad Fachry; Saleh, Anis; Alisyahbana, Takdir; Safutra, Nur Ihwan; Nusran, Muhammad (Journal of Industrial Engineering Management, 2021)
One of the global problems related to the future of cities is the environmental problem, namely the amount of municipal solid waste. From this waste, several issues arise in various aspects, such as health, aesthetics, and social and environmental problems. So that focused research is carried out on the management of urban solid waste produced by households. The research objective is to design a conceptual model and determine the variables and indicators that affect the generation of urban household solid waste and determine what prevention can be done. The model intended consists of 5 variables and 17 indicators. Data was collected based on a survey method with a closed questionnaire distributed to 120 respondents aged ≥ 17 years and residing in Yogyakarta. Analysis of the model and variable relationships was carried out based on the Structural Equation Modeling (SEM) method with the help of AMOS 24 software. The results showed that the designed model was valid. Socioeconomic variables, KAP level, waste reduction, and seasonality are direct predictors determining waste generation behavior. Socioeconomic variables are also direct predictors of KAP level and seasonal variables, and KAP level variables are direct predictors of waste reduction and seasonal variables